Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di BEI tahun 2013-2017) - Mutammimah Mutammimah (MAKSIMUM, 2019)
The Company Value is a measure of the success of the company's management in the prospect of future operations so that it can realize the trust of the company's shareholders. The company value becomes very important because the high Company Value indicates the high prosperity of the shareholders. This research aims to determine the effect of Managerial Ownership, Dividend Policy, Debt Policy, Company Size, Company Growth and Profitability on Company Value in manufacturing companies listed on the Indonesia Stock Exchange (BEI) in 2013-2017.      The population of this research is all manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The sampling method used purposive sampling, which is a sampling method based on certain criteria and 70 datas selected as samples, and hypothesis testing used multiple regression analysis. The results of this study indicated that partially independent variables Managerial Ownership, Dividend Policy, Company Size, Company Growth have no significant effect on the Company Value, while Debt Policy and Profitability have a significant effect on Company Value. And the test of the coefficient of determination shows a number of 0.361, it indicates that simultaneously independent variables of Managerial Ownership, Dividend Policy, Debt Policy, Company Size, Company Growth, and Profitability are able to explain the dependent variable Company value is about 36,1%, while the remaining 63,9% is explained by other variables.